ANALISIS WACANA IDEOLOGI BAHASA PEREMPUAN - Firman Firman (LPPM IAIN Parepare, 2016)
Women’s language must be considered as a discourse, meaning that it is a way to express or to articulate events, experiences, views, and certain facts of life. Women’s language always represents an attitude toward certain life view, precisely in the form of a description of a contribution of whole worldview to the idea of life which have been recognized and interpreted by women. In fact, women’s and men’s languages are different but other opinion states the reverse. Women’s language tends to use cooperative style of speech, while men’s language employs competitive style. Men and women may be separated by dichotomy between private and public, or production and reproduction. As a result, the separation leads to the different attitude of men and women toward speech.An ideology can be expressed through language in the form of discourse. Ideology may be given explicitly or implicitly, even with or without awareness of the ideology carrier. Such condition has been experienced by women during the revelation of their ideology. A medium to deliver ideology is discourse, but still may involve the consideration of vocabulary and grammar selections.